Integration of the Pancasila Student Profile Values in Islamic Religious Education and Character Education to Strengthen Independent and Creative Student Characters - Azizah, Nur; Sa’adi, Sa’adi; Miftahuddin, Miftahuddin (Rausyan Fikri Journal of Islamic Studies, 2025)
The study aims to analyze the insertion of independent and creative values within the Islamic Religious Education and Character Education subject at SMP Cahaya Qur’an. This research employs a qualitative descriptive approach with a case study design. Data were collected through interviews, documentation, and observations related to activities that have been conducted. The findings indicate that the insertion of the Profil Pelajar Pancasila values in the Islamic Religious Education and Character Education subject is carried out through religious activities integrated within the boarding school system and implemented based on project-based learning involving the creation of digital works such as e-flyers and videos related to Islamic Religious Education and Character Education materials and attitudes of independence in activities like prayer, personal hygiene, self-management, and learning commitment. This study contributes to the development of educational models fostering independence and creativity in realizing the Pancasila Student Profile. Limitations of this study include its scope restricted to one school and a focus on only two values of the Pancasila Student Profile, thus the results cannot be widely generalized and further studies with larger samples and varied values are recommended.